Un indice del Liber Aksumae - Bausi, Alessandro (Aethiopica, 2006)
To the difference of previous partial indexes of Liber Aksumae (e.g., by G.W.B. Hunt-ingford), the present one puts together all the proper names and noteworthy terms occurring in the famous publication by C. Conti Rossini of 1909-10. The index refers to the translation volume and is intended as a simple working tool for all those (archaeologists, historians, philologists, linguists etc.) who may be interested in retrieving informa-tions preserved in one of Ethiopia’s richest ‘archival’ documentary sources.